Utilization of Probiotics in Treatment of Gastrointestinal Infections among Children: Probiotics in Treatment of Gastrointestinal Infections among Children - Fatima, Azka; Khan, Salsbeel (Pakistan BioMedical Journal, 2022)
Probiotics have been extensively studied and examined globally. Probiotics are extremely important for human health and encourage the growth of good bacteria in the human body. Probiotics exert its beneficial effect in the human body through a number of mechanisms, including the production of antibacterial chemicals, the eradication of pathogenic bacteria, and the prevention of the synthesis of toxic substances. Probiotics are now available in the market as functional foods and dietary supplements. The probiotics market is expected to increase from 35.6 billion in 2015 to 64.6 billion in 2023. Lactobacillus and Bifidobacteria are the most commonly used probiotics in the infant formulas. Probiotics are extremely beneficial for the gut health. Various factors disrupt the microflora of gastrointestinal tract of infants and cause various GI infections and diseases. Methods: Previous articles have been studied to develop this review article about a broad spectrum of pediatric disorders treated with probiotics. Probiotics are helpful in the prevention of irritable bowel syndrome, constipation, diarrhoea, gastrointestinal reflux disease, inflammatory bowel disease, acute gastroenteritis, infantile colic and necrotizing enterocolitis. Different types of probiotic mixtures and probiotic bacteria are utilized in the treatment of GI diseases. Probiotics have also proved its effectiveness in the treatment of gastrointestinal conditions. Conclusion: Efforts to improve human health are concentrating on methods for modifying the indigenous microflora using live microorganisms, now referred to as “probiotics”. The probiotic market is expanding and is expected to rise to 64.6bn by the year 2023. Probiotics are now added to a variety of food products such as cereals, fruit juices and milk-based product